Pengaruh Pola Asuh Orang Tua Terhadap Hasil Belajar Siswa Kelas X Mata Pelajaran Ekonomi di SMA Negeri 3 Muaro Jambi - Ferdiansyah, M.; Iqbal Jamaluddin, M.; Alvionita, Havizah (SJEE (Scientific Journals of Economic Education), 2025)
This study aims to determine the influence of parenting patterns and learning outcomes of class X students of SMA Negeri 3 Muaro Jambi. The research method used in this study is a quantitative method using a simple linear regression analysis technique. The research subjects were students of SMA Negeri 3 Muaro Jambi with a sample of 149 students. The results showed that there was an influence of parenting patterns on learning outcomes in class X of SMA Negeri 3 Muaro Jambi. The results of the study obtained that the constant results of learning outcomes without the influence of independent variables were 59.572. While the magnitude of the influence of the parenting pattern variable was 0.196 with a significance of 0.005. The t count was 3,564 with a t table of 1.655.